Hubungan Tingkat Stres Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Terapi Hemodialisis Di Rsud Undata Provinsi Sulawesi Tengah - Auliyah Dif Hardi; Siti Yartin; Abdul Rahman (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Chronic kidney failure is a disease that causes a decline in kidney function, making the kidneys unable to filter and remove electrolytes, regulate fluid and chemical balance (such as sodium and potassium in the blood), and produce urine. Patients undergoing hemodialysis experience psychosocial problems such as anxiety about their unpredictable illness, financial and employment issues, impotence, family responsibilities, and even fear of death, as they must undergo lifelong hemodialysis, which greatly affects their quality of life. Objective: The purpose of this study was to determine the relationship between stress levels and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy at Undata Regional General Hospital, Central Sulawesi Province. Methods: This study used a quantitative method with a cross-sectional design. The study population consisted of 173 hemodialysis patients at Undata Regional General Hospital, Central Sulawesi Province. From this number, 57 hemodialysis patients were selected as samples. The sampling technique used was purposive sampling, and the statistical test applied was the gamma test. Results: The univariate analysis of the 57 respondents showed that most experienced moderate stress (42 respondents, 73.7%) and tended to have a low quality of life (41 respondents, 71.9%). The bivariate analysis using the gamma test showed a significant relationship between stress levels and quality of life, with a p-value of 0.024. Conclusion: There is a significant relationship between stress levels and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy.